ANALISIS STANDAR PELAYANAN MINIMUM ANGKUTAN ORANG DENGAN KERETA API DI STASIUN (STUDI KASUS: STASIUN KUTOARJO) - , WAHYUDIN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The train station is a place/meeting point between highway transportation modes with railway transportation modes. In its implementation, the railway station should be equipped with the facilities needed by the station users, which is included in the ministerial regulation on minimum service standards (SPM) in the PM 9, 2011. The rules are not fully implemented yet by the organizers of the station, and these services still have not illustrated the needs for station users. Therefore, there should be a study to determine how much the service provided by the station operators accordingly to SPM and judgment of the user and userâs needs that have not been presented in the SPM. The study was conducted by survey of the service performance provided Kutoarjo station, and then compared with the benchmarks contained in the SPM. This research was also conducted via interviews to see how much the assessment of users of the existing service performance, and then finding the relation between interviews result and userâs characteristic was performed based on the chi-square test. The interview survey was also conducted to determine the level of need for facilities that have not been included in the SPM. From the results with SPM performance analysis, it was found that there was a kind of service in Kutoarjo station that did not meet minimum service standards, namely: service time at the reservation counters still over 30 seconds that is 150.97 seconds, the seating area is still under 0.6 m 2 that is 0.4 m 2 , and the toilets are still less than 6 normal room and 2 disabled room for both men and women. From the analysis of user-rated performance, it was found that the majority of respondents assessed the service performance of the station was sufficient conditions and the information facility was clear conditions. From the results of the chi-square test, there was a relationship between respondentâs age with waiting room facilities assessment, types of work of respondent with toilet facilities assessment, trip origin of respondent with class of service information and a map of the railway network assessment, trip destination of respondent with passengerâs facilities for getting in/out and safety and security facilities assessment, trip purpose of respondent with counter facilities, health facilities and safety and security facilities assessment, education level of respondent with assessment of parking facilities, and the level of income of respondent with the assessment of health facilities. From the analysis of the needs of the service, it was found that the ATM facilities, shops, hotel booking services, transport, travel agencies, internet, lockers / storage of goods, hall, arrival and departure curbs, public phones, and hand-phone charging facilities were needed by the majority of respondents.